Medication adherence in young adults with youth-onset type 2 diabetes: iCount, an observational study. (February 2022) - Trief, Paula M.; Kalichman, Seth C.; Wang, Dongliang; Drews, Kimberly L.; Anderson, Barbara J.; Bulger, Jane D.; Weinstock, Ruth S.
Highlights: Almost 70% of young adults with youth-onset type 2 diabetes were low-adherent to oral medications. Approximately one-third of young adults were low-adherent to insulin. Non-Hispanic Blacks, women and those without healthcare coverage were at greatest risk for poor adherence. Given poor outcomes, medication adherence interventions that work for this group are needed. Abstract: Aims: To assess prevalence of, and factors associated with, medication adherence of young adults with youth-onset type 2 diabetes. Methods: Oral hypoglycaemia agent (OHA) adherence was measured with unannounced telephone pill counts, insulin adherence was self-reported. Those taking ≥ 80% of pills/insulin were classified "high-adherent, " <80% of pills/insulin "low-adherent." Analyses included unadjusted, and adjusted linear and logistic regressions assessing associations of participant factors with adherence. Results: For people taking OHAs (N = 212, mean age 26 yrs, 67% women, 18% non-Hispanic White, 35% non-Hispanic Black, 41% Hispanic), 69.8% were low-adherent. HbA1c was lower in the high-adherent group (9.2%/77 mmol/mol vs. 10.0%/86 mmol/mol, p < 0.04). More non-Hispanic Blacks were low-adherent (85.7%) than Hispanics (60.2%) and non-Hispanic whites (55.3%, p < 0.002); 91.4% of participants without healthcare coverage were low-adherent vs. 65.5% of those with coverage (p < 0.004). After adjustment, gender (p = 0.024), race/ethnicity (p < 0.001) and healthcare coverage (p = 0.001) remained related to OHA adherence. For insulin (N = 192), 37% were low-adherent. HbA1c was associated with insulin adherence (low = 11.2%/99 mmol/mol vs. high = 10.0%/86 mmol/mol, p < 0.001) with and without adjustment. Conclusions: Young adults with youth-onset type 2 diabetes, especially females, non-Hispanic Blacks and those without healthcare coverage, commonly had low-OHA adherence. Glycaemic control was also poor. Interventions to improve medication adherence are needed for this vulnerable group.